1995
DOI: 10.1055/s-2006-958048
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis and Biological Activity of Leptocarpin and Leptocarpin Acetate

Abstract: Letters a group of PAHs are present in the plant extract and contributed to the light-mediated antiviral activity. We believe that the source of the PAHs was not from contamination in the purification procedure. With separation and analytical techniques capable of purifying trace components, it is more of a possibility that impurities from materials used in the processing can be accumj.ilated and be found in an identifiable quantity. The major solvent used in this procedure consisted of a mixture of hexanes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…LTC is a sesquiterpene lactone, a major component of the Asteraceae family [ 25 ]. According to Martinez et al [ 12 ], LTC exhibits high cytotoxicity on human liver adenocarcinoma (SK-Hep-1) and HeLa cells. Therefore, LTC has anti-cancer and anti-tumor effects [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTC is a sesquiterpene lactone, a major component of the Asteraceae family [ 25 ]. According to Martinez et al [ 12 ], LTC exhibits high cytotoxicity on human liver adenocarcinoma (SK-Hep-1) and HeLa cells. Therefore, LTC has anti-cancer and anti-tumor effects [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asteraceae, which produces many bioactive compounds such as polyacetylenes, diterpenes, and sesquiterpene lactones [ 8 ], expresses various clinical activities, including anti-tumor, anti-ulcer, anti-inflammatory, neurocytotoxic, and cardiotonic activities [ 9 , 10 ], as well as the ability to influence critical biological processes such as cell signaling, cell proliferation, apoptosis, and mitochondrial metabolism [ 11 ]. Leptocarpin (LTC) is the one of the major components of Leptocarpha rivularis , which belongs to the Asteraceae family and was been widely used as a folk remedy [ 12 14 ]. In our study, LTC was used as an anti-tumor drug to treat MG63 cells.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, SQL exhibit cytotoxic activity against various cancer cell lines, and therefore the activity of these extracts must be related to their SQL content. In previous work, it has been found that L. rivularis contains a high percentage of SQL, and leptocarpin amounts to approximately 0.02% of the EA extract whereas the content of LTC in the ET extract is even lower 23,24 . To explain the origin of extract's activities the values of IC 50 obtained for EA extract are compared with reported LTC cytotoxicity (last column in Table 1) and discussed as a function of LTC content.…”
Section: Ic50 G/mlmentioning
confidence: 93%
“…Thus, a comparison of IC 50 values obtained for extracts with those reported for LTC (last column in Table 1) suggest that the activity of extracts is due to LTC and other secondary -secbutyl leptocarpin; rivularin; 8 -angeloyl-1 ,3 -dihydroxy-4,10-dimethyl-11 (13) methylen-4Z,9Z-dienheliangol-6,12-olide (4); and 8 -angeloyl-1 ,3dihydroxy-4-methyl-11 (13) 10 14-dimethylen-4Z-enheliangol-6,12-olide (5). All these lactones were isolated from the EA extract, except for 4 and 5 that have been not isolated due to the low percentage in which they are present 23,24,47 .…”
Section: Ic50 G/mlmentioning
confidence: 99%
See 1 more Smart Citation